SP140 regulates the expression of immune-related genes associated with multiple sclerosis and other autoimmune diseases by NF-κB inhibition. (8th August 2018) - Karaky, Mohamad; Fedetz, María; Potenciano, Victor; Andrés-León, Eduardo; Codina, Anna Esteve; Barrionuevo, Cristina; Alcina, Antonio; Matesanz, Fuencisla
Abstract: SP140 locus has been associated with multiple sclerosis (MS) as well as other autoimmune diseases by genome-wide association studies (GWAS). The causal variant of these associations (rs28445040-T) alters the splicing of the SP140 gene transcripts reducing the protein expression. We aimed to understand why the reduction of SP140 expression produced by the risk variant can increase the susceptibility to MS. To this end, we determined by RNA sequencing (RNA-seq) analysis the differentially expressed genes after SP140 silencing in lymphoblastoid cell lines (LCLs). We analyzed these genes by gene ontology (GO), comparative transcriptome profiles, enrichment of transcription factors (TFs) in the promoters of these genes and colocalization with GWAS risk variants. We also monitored the activity of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κ B) in SP140- silenced cells by luciferase reporter system. We identified 100 genes that were up-regulated and 22 genes down-regulated in SP140- silenced LCLs. GO analysis revealed that genes affected by SP140 were involved in regulation of cytokine production, inflammatory response and cell–cell adhesion. We observed enrichment of NF-κ B TF in the promoter of up-regulated genes and NF-κ B-increased activity in SP140- silenced cell lines. We showed enrichment of genes regulated by SP140 in GWAS-detected risk loci for MS (14.63 folds), Crohn's disease (4.82 folds) and inflammatory bowel disease (4.47 folds), not observed in other unrelated immune diseases. Our findings showed that SP140 is an important repressor of genes implicated in inflammation, suggesting that decreased expression of SP140, promoted by the rs28445040-T risk variant, may lead to up-regulation of these genes by means of NF-κ B inhibition in B cells.